Feline Interstitial Cystitis Enhances Mucosa-Dependent Contractile Responses to Serotonin - Ikeda, Youko (Int Neurourol J, 2018)
PURPOSE: To determine whether responses to serotonin are altered in bladder strips from cats diagnosed with a naturally occurring form of bladder pain syndrome/interstitial cystitis termed feline interstitial cystitis (FIC). METHODS: Full thickness bladder strips were isolated from aged matched healthy control cats and cats with clinically verified FIC. Bladder strips were mounted in an organ bath and connected to a tension transducer to record contractile activity. A serotonin dose response (0.01–10μM) was determined for each strip with the mucosa intact or denuded. RESULTS: Bladder strips from control and FIC cats contracted in response to serotonin in a dose-dependent manner. The normalized force of serotonin-evoked contractions was significantly greater in bladder strips from cats with FIC (n=7) than from control cats (n=4). Removal of the mucosa significantly decreased serotonin-mediated responses in both control and FIC bladder preparations. Furthermore, the contractions in response to serotonin were abolished by 1μM atropine in both control and FIC bladder strips. CONCLUSIONS: The effect of serotonin on contractile force, but not sensitivity, was potentiated in bladder strips from cats with FIC, and was dependent upon the presence of the mucosa in control and FIC groups. As atropine inhibited these effects of serotonin, we hypothesize that, serotonin enhances acetylcholine release from the mucosa of FIC cat bladder strips, which could account for the increased force generated. In summary, FIC augments the responsiveness of bladder to serotonin, which may contribute to the symptoms associated with this chronic condition.